Regulation of Hippocampal Synaptic Function by the Metabolic Hormone, Leptin: Implications for Health and Neurodegenerative Disease - McGregor, Gemma; Harvey, Jenni (Frontiers in Cellular Neuroscience, 2018)
The role of the endocrine hormone leptin in regulating food intake and body weight in the hypothalamus are well documented. However the CNS targets for leptin are not restricted to the hypothalamus as high levels of leptin receptor expression are evident in several brain regions involved in higher cognitive functions including the hippocampus. Numerous studies have identified a cognitive enhancing role for leptin in the hippocampus as exogenous application of this hormone facilitates hippocampal-dependent learning and memory, whereas lack or insensitivity to leptin results in significant memory deficits. Leptin also markedly influences the key cellular events that are implicated in learning and memory including activity-dependent hippocampal synaptic plasticity and glutamate receptor trafficking. Like other metabolic hormones, there is a significant decline in neuronal sensitivity to leptin with age as the ability of leptin to regulate hippocampal synaptic function is substantially reduced in aged compared to adult. Clinical studies have also identified a link between leptin and neurodegenerative disorders such as Alzheimer’s disease (AD). Thus the leptin system may be a novel target for developing therapies to treat AD. In support of this, accumulating evidence indicates that leptin has cognitive enhancing and neuroprotective actions in various models of AD. Here we review the evidence that leptin is a potent regulator of hippocampal synaptic function, and discuss how age-related alterations in this hormonal system influences neurodegenerative disease.